PROFESSIONAL SELF-DETERMINATION OF MOSCOW YOUTH: SOCIOLOGICAL ANALYSIS - E. Tikhonova; E. Dianina (Вестник университета)
The article considers the problem of primary professional self-determination of youth. Also it presents the results of a sociological survey aimed at investigating factors influencing professional self-determination among Moscow senior and high school students and at specification the role of the existing career guidance system in Moscow schools in this process. The survey has revealed the role of subjective and objective factors influencing Moscow students' future career choice, as well as the range of problems in the organization of career guidance in Moscow schools